GENOTYPE CHARACTERISTICS OF PATHOGENIC Escherichia coli BACTERIA ISOLATED FROM DUMAI SEA WATER - Sophia Rahmah Saleha; Feliatra Feliatra; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted from March until April 2019. The purpose of this study was to examine the resistance of E. coli bacteria toward antibiotics (ciprofloxasin, streptomycin and erythromycin) and to identify isolated from Dumai seawaters the bacteria genotypes. Resistance test showed that isolated E1, E4, E6, E8, E11, E13, and E15 were resistant to antibiotic streptomycin and erythromycin with inhibitory zones ranging from 2.9 to 5.9 mm. While sensitivity to ciprofloxasin indicated the inhibition zones of 22.1 mm. Analysis of E. coli by using PCR method technique 16S sequences found three strains of bacteria had the highest homologi levels, those were E. coli strain NBRC 102203, E. coli strain JCM 1649 and E. coli strain U 5/41. E1-2 isolate has similarity to E. coli strain NBRC 102203, E4-2 and E6-2 isolates are similar to E. coli strain JCM 1649, E8-2 isolate to strain NBRC 102203, E11-2 isolates to E. coli strain U 5/41, E13-2 and E15-2 isolates to strain NBRC 102203. Keyword : Escherichia coli, Resistance, Antibiotics, Genotype, Sekuens 16S rRNA